A nomogram for predicting cancer-specific survival and overall survival in elderly patients with nonmetastatic renal cell carcinoma - Zhanghuang, Chenghao; Wang, Jinkui; Zhang, Zhaoxia; Yao, Zhigang; Ji, Fengming; Li, Li; Xie, Yucheng; Yang, Zhen; Tang, Haoyu; Zhang, Kun; Wu, Chengchuang; Yan, Bing (Frontiers in Surgery, 2023)
Background: Renal cell carcinoma (RCC) is a common malignant tumour in the elderly with an increasing trend in recent years. We aimed to construct a nomogram of cancer-specific survival (CSS) in elderly patients with nonmetastatic renal cell carcinoma (nmRCC). Methods: Clinicopathological information was downloaded from the Surveillance, Epidemiology, and End Results (SEER) program in elderly patients with nmRCC from 2010 to 2015. All patients were randomly assigned to a training cohort (70%) or a validation cohort (30%). Univariate and multivariate Cox regression analyses were used to identify independent risk factors for patient outcomes in the training cohort. A nomogram was constructed based on these independent risk factors to predict the 1-, 3-, and 5-year CSS in elderly patients with nmRCC. We used a range of methods to validate the accuracy and reliability of the model, including calibration curve, consistency index (C-index), the area under the receiver operating curve (AUC). Decision curve analysis (DCA) was used to test the clinical utility of the model. Results: A total of 12,116 patients were enrolled in the study. Patients were randomly assigned to the training cohort (N=8514) and validation cohort (N=3602). In the training cohort, univariate and multivariate Cox regression analysis showed that age, marriage, tumour histological type, histological tumour grade, TN stage, tumour size, surgery are independent risk factors for prognosis. A nomogram was constructed based on independent risk factors to predict CSS at 1-, 3-, and 5- years in elderly patients with nmRCC. The C-index of the training cohort and the validation cohort were 0.826 and 0.831, respectively. The AUC results of the training and validation cohort were similar to the C-index. The calibration curve indicated that the observed value is highly consistent with the predicted value, meaning the model has good accuracy. DCA results suggest that the clinical significance of the nomogram is better than that of traditional TNM staging. Conclusions: We built a nomogram prediction model to predict the 1-, 3- and 5-year CSS of elderly nmRCC patients. This model has good accuracy and discrimination and can help doctors and patients make clinical decisions and active monitoring.